RATIONALITY OF THE USE OF NSAIDS IN rheumatic OSTEOARTHRITIS PATIENTS AT THE PUSKESMAS SINGOSARI, PEMATANGSIANTA CITY, JANUARY FEBRUARY 2019 PERIOD - I Ngurah Gede Verar Fujastawan; Mustaruddin; Beta Hanindiya; Dian Permata Nasution; Ismi Noer Fadilah; Hendri Kurniawan; Marthalea Erbin Nahak; Bernido Raflo Purba (Universitas Efarina, 2022)
Osteoarthritis (OA) is the most common form of arthritis found in the community, is chronic in nature, has a major impact on public health issues. a total of 213 arthritis patients, only 30 patients who met the inclusion criteria were due to incomplete medical record data or even loss of medical record data which caused the patient's medical record data to be incomplete. As for the aspect of rationality in terms of 6 accuracy (right diagnosis, right indication, right drug, right dose, right route of administration, right patient) then the results of the analysis show that accuracy is 100% right, while for the exact parameters of the drug is still worth 53%. So it can be concluded that treatment for osteoarthritis patients when viewed from the right diagnosis, right indication, right dose, right patient, right drug, right method of administration at the Singosari Health Center cannot be fully rational.